Geogenic nickel exposure from food consumption and soil ingestion: A bioavailability based assessment. (October 2020) - Li, Hong-Bo; Wang, Jue-Yang; Chen, Xiao-Qiang; Li, Yu-Ping; Fan, Jian; Ren, Jing-Hua; Luo, Xiao-San; Juhasz, Albert L.; Ma, Lena Q.
Abstract: Accumulation and oral bioavailability of nickel (Ni) were rarely assessed for staple crops grown in high geogenic Ni soils. To assess exposure risk of geogenic Ni, soil, wheat, and rice samples were collected from a naturally high background Ni area and measured for Ni oral relative bioavailability (RBA, relative to NiSO4 ) using a newly developed mouse urinary Ni excretion bioassay. Results showed that soils were enriched with Ni (80.5 ± 23.0 mg kg −1, n = 58), while high Ni contents were observed in rice (2.66 ± 1.46 mg kg −1 ) and wheat (1.32 ± 0.78 mg kg −1 ) grains, with rice containing ∼2-fold higher Ni content than wheat. Ni-RBA was low in soil (14.8 ± 7.79%, n = 18), but high in wheat and rice with rice Ni-RBA (85.9 ± 19.1%, n = 9) being ∼2-fold higher than wheat (46.1 ± 21.2%, n = 16). A negative correlation ( r  = 0.61) was observed between Ni-RBA and iron content in rice and wheat, suggesting the low iron status of rice drives its high Ni bioavailability. The higher Ni accumulation and bioavailability for rice highlights that rice consumption was a more important contributor to daily Ni intake compared to wheat, while Ni intake from direct soil ingestion was negligible. This study suggests a potential health risk of staple crops especially rice when grown in high geogenic Ni areas. Graphical abstract: Image 1 Highlights: Geogenic Ni exposure via food consumption and soil ingestion was assessed. Elevated Ni was observed in soil and rice/wheat at a high geogenic Ni area. Rice accumulated ∼2-fold higher Ni content than wheat when grown in rotation. Oral bioavailability of rice-Ni was ∼2-fold higher than that of wheat-Ni. Rice consumption was the predominant contributor to Ni exposure. Abstract : Geogenic Ni exposure via food consumption and soil ingestion was assessed by analyzing Ni concentration and oral bioavailability in soil, wheat, and rice.